Determinants and Correlates of Depression in Psoriasis Patients: Does Marital Adjustment Play a Role? - Priyanka Sharma; Deepak Sharma; Abdul Qadir Jilani (Indian Journal of Private Psychiatry)
Aim: To assess the prevalence and severity of depression in married psoriasis patients and to determine its correlates with special reference to marital adjustment. Materials and methods: A total of 50 patients with a history of psoriasis for more than or equal to 2 years (age range, 26–45 years; mean age, 33.0 ± 5.61 years; 80% males) were enrolled in the study. The prevalence and severity of depression were assessed using the Hamilton depression rating scale (HDRS), and the severity of psoriasis was assessed using the psoriasis area and severity index (PASI). The marital adjustment was assessed using the marital adjustment questionnaire (MAQ). Multivariate linear regression was performed to find out independent factors related to HDRS. Results: Mean HDRS was 10.06 ± 5.25. Mild, moderate, and severe depression was seen in 46%, 18%, and 6% of patients, respectively. On multivariate linear regression, after adjusting for age, sex, place of residence, occupation, socioeconomic status, duration of marriage, number of children, BMI, psoriasis type, and duration of psoriasis, only PASI scores (p = 0.035) and MAQ scores (p < 0.001) emerged as factors independently associated with HDRS score (r2 = 0.602). In a reduced linear regression model, both PASI scores and MAQ scores were significantly associated with HDRS (r2 = 0.527). Conclusion: Depressive symptoms were common in psoriasis patients and were associated with psoriasis severity (PASI). Marital adjustment offered a protective effect against depressive symptoms.